THE EFFECT OF ANIMATION MOVIE AGAINST ANXIETY LEVEL IN DENTAL TREATMENT OF ELEMENTARY SCHOOL 15 PADANG STUDENT - Fitriana, Aida; Noer, Mustafa; Rabiansyah Pratama, Afriza (Fakultas Kedokteran Gigi Unjani, 2025)
Anxiety, a normal condition which part of human development that happen from childhood. Dental anxiety has been studied for 10 years ago and still be the basic problem for dental treatment. Distraction is a technique to manage dental anxiety. Distraction is a method to distract patient to something that patient like. Audiovisual distraction is one of many techniques that effective to use for children. One of the idea to distract children to watch animation movie. This study use post test only control group design. This study use 50 samples. The anxiety level is measured by blood pressure, breathing, heartbeat, psychological sign, and physiological sign when student being treated for dental plaque record. Based on Kolmogorov-smirnov test, the result showed that there was an effect of animation movie for dental treatment with value of p<0.05 compare to control group. The conclusion of this study is animation movie have an effect against anxiety level in dental treatment. DOI : 10.54052/jhds.v4n3.p223-238